The Life Cycle Of A Chalcocite Heap Bioleach System (The Minerals, Metals and Materials Society, 2003)
A full-scale test of chalcocite heap bioleaching was undertaken at Straits? Nifty Copper Operation. Straits worked closely with the CSIRO to investigate the chemical and biological changes over the life cycle of this chalcocite heap bioleach system. Results indicated nearly 80% copper recovery was achieved in just over 300 days. Significant changes in iron chemistry and microbiological activity were detected. Temperatures in the heap reached as high as 70 ºC during the time of maximal copper recovery rate. The dominant cultivatable bacterial strains were typical mesophilic bacteria, however, naturally occurring moderately thermophilic bacteria were detected by culture and culture independent molecular (PCR followed by denaturing gradient electrophoresis [DGGE]) and signature lipid methods. Signatures for the iron and sulfur-oxidising species Acidithiobacillus ferrooxidans and Sulfobacillus spp., as well as the moderately thermophilic heterotroph Alicyclobacillus sp. were detected. Biomass was greatest in ?warm? but not ?hot? parts of the heap, and Hyperthermophilic Archaea were not detected.